IPPAR Model Pendekatan Konten Kreator dalam Strategi Meraih Engagement di Sosial Media pada Channel YouTube Selontok Fish Official - Sahdan, Sahdan; Maharani, Dwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to reveal the content strategy of Selontok Fish Official in achieving engagement on social media, particularly on their YouTube channel. Employing a qualitative approach, the study investigates the object naturally, with the researcher serving as the primary instrument. The analysis techniques involve SWOT Analysis and IPPAR Model, and the data analysis is inductive. The research focuses on content strategy, especially the use of the Palembang language, and overcoming production constraints with innovative solutions. The conclusion highlights the success of the creative team Selontok Fish Official, originating from individual efforts, their vision in the Palembang language, and efforts to promote local cultural richness. With hopes for continuous growth, achieving higher milestones, and providing economic benefits to the team and community, this research demonstrates that success in the creative content realm can generate a broad positive impact.